Taxonomic revision of living boring bivalves belonging to the family Pholadidae Lamarck, 1809, (Bivalvia: Myida) from South western Atlantic - Delfino, Marina Inés (2021)
Boring bivalves of the family Pholadidae Lamarck, 1809 living in Argentinean and Uruguayan waters are herein revised. The literature research revealed twelve nominal species of Pholadidae mentioned as living in the study area. Type material of all nominal taxa were examined when it was possible. Additional specimens from field works and malacological collections were studied, illustrated and re-described. Details of type localities, repositories, and distribution range are provided for each valid taxa. This work revealed the presence of five native and one introduced species belonging to Pholadidae in Argentinean and Uruguayan waters. Barnea (Anchomasa) lamellosa, Cyrtopleura (Scobinopholas) lanceolata, Pholas (Thovana) campechiensis and Martesia fragilis belonging to the Argentine biogeographical province; Netastoma darwinii from Magellan province; and Barnea (Anchomasa) truncata introduced in the Bahía Blanca estuary. Finally, morphological comparison with congeneric species distributed in American seas are provided.